Programs and Fields of Youth Empowerment in Abu Dhabi: Qualitative study - Alhammadi, Fatma Abdulla; Al-Gharaibeh, Fakir (Al-Adab Journal, 2020)
This study aimed to analyze the content of youth empowerment programs in the Emirate of Abu Dhabi, by identifying the empowerment programs offered by government institutions in the Emirate of Abu Dhabi, and what are the areas of empowerment that these programs focus on in addition to the degree of availability of the dimensions of empowerment in each of the areas of (social and Economic and Participate in decision-making and respect other), as this study used the descriptive analytical approach, and the research sample was in (26) youth empowerment programs in the authorities responsible for those programs in the Emirate of Abu Dhabi.The most important findings of the research were that youth empowerment programs in the Emirate of Abu Dhabi are provided by entities at the federal level, and some by local entities, and that youth empowerment areas is multiple and varied, with social empowerment at the rate of (47.2%), then economic empowerment at (31.6%), Then Participate in decision-making and respect other (21.2%) in addition to that the social empowerment focused on developing problem-solving skills and skills to face challenges while the economic empowerment focused on developing professional skills and investing the energies of young people and employing their talents while the participate in decision-making and respect other focused on equal opportunities available for young people in programs and gender equality.